Effects of Zn pollution on soil: Pollution sources, impacts and solutions - Huu-Tap Van; Van Hung Hoang; Luong Thi Quynh Nga; Van Quang Nguyen (Results in Surfaces and Interfaces)
The management of zinc (Zn) pollution in soil and its environmental impact is a critical concern that requires a comprehensive approach. This article presents a synthesis of research on assessing and managing Zn pollution, encompassing environmental regulation, pollution control technologies, land use management, and research and development efforts. The potential ecological risk of heavy metal pollution, including Zn, is evaluated using various assessment methods. Phytoremediation, soil washing, and agricultural practices are proposed as effective strategies for reducing Zn pollution and protecting land and the environment. The impact of Zn pollution on soil microbial communities, ecological risk assessment, and the potential for physiological integration to alleviate heavy metal stress are also discussed. The article emphasises the importance of interdisciplinary approaches to environmental remediation and the need for sustainable management practices to mitigate the impact of Zn pollution on ecosystems. The expected outcome of this work is the development of more effective and sustainable Zn pollution management strategies, ultimately reducing ecological risks and enhancing soil health for long-term environmental protection. The utility of this study lies in its comprehensive evaluation of Zn pollution management strategies, highlighting both existing and emerging solutions to mitigate its adverse environmental effects.